2020
DOI: 10.3389/fpsyt.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of the Correlation Between Previous Hospitalizations, the Type of Current Living Space, and Quality of Family Function

Abstract: Background and Aim: There are important public health issues involving rehabilitation of patients living with schizophrenia in the community. The purpose of this study was to analyze the correlations between number of previous hospitalizations, living space and quality of family function in the rehabilitation of patients living with schizophrenia in the community. The study attempts to determine the potential ways to use beneficial factors in recurrent hospitalization for improving treatment and rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…A meta-analysis showed that individuals who will later develop schizophrenia had a poorer general academic and mathematic achievement than those who will not and were less likely to enter higher education [33]. Women living with schizophrenia are more likely than men to continue their education [34]. Our results did not identify the educational or professional level as being statistically relevant to impact as a risk or protective factor regarding the number of hospitalizations.…”
Section: Conflict Of Interest: None Declaredcontrasting
confidence: 71%
“…A meta-analysis showed that individuals who will later develop schizophrenia had a poorer general academic and mathematic achievement than those who will not and were less likely to enter higher education [33]. Women living with schizophrenia are more likely than men to continue their education [34]. Our results did not identify the educational or professional level as being statistically relevant to impact as a risk or protective factor regarding the number of hospitalizations.…”
Section: Conflict Of Interest: None Declaredcontrasting
confidence: 71%
“…Studies have demonstrated that chronically hospitalised individuals have higher rates of singleness, marital discord, separation, and divorce than the general population (Breslau et al., 2011; Bursalioglu et al., 2013). For patients, unmet emotional needs and negative attitudes towards marriage during hospitalisation can impede functional recovery by reducing psychological resilience and treatment compliance (Fan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%